Der Traum als Raum politischer Bildung in der Kinder- und Jugendliteratur - Mehrbrey, Sophia (KulturPoetik, 2022)
Based on an international corpus of children and young adult fiction, I would like to explore the question of how ‘the political’ is articulated in these texts and what role dreams play for the discussion of political ideas. Dream narratives blur the boundary between reality and fiction and thus create a virtual space in which the young protagonists can experience themselves. Since modernity, children and young adult literature is supposed to address the process of personality development of both, the juvenile heroes and readers. On closer inspection, however, one realises that the articulation of personal dilemmas is often linked to social and political issues. This paper thus aims to investigate the interaction of the political and the personal, which places the ethical moment at the centre of political discourse, within the fictional dream worlds.